The effectiveness of the team quiz type cooperative learning model on the learning outcomes of class XI students in geography subjects at SMAN 4 Palu - Nurhaliza, Sitti; Hasan, Haslita Rahmawati; Listiqowati, Ika; Suwarni (Journal of Geography Science and Education, 2025)
This study aims to determine the influence of the Team Quiz type cooperative learning model on student learning outcomes at SMAN 4 Palu. This study uses a quantitative research method with the type of Quasi Experimental research. Data collection techniques that include observations, tests, and documentation to determine student learning outcomes using a team quiz-type cooperative learning model. The research sample consists of two classes, namely an experimental class that applies the Team Quiz model and a control class that uses the Discussion learning method. Data was collected through learning outcome tests conducted before and after the implementation of the learning model. Data analysis was carried out with a test (t-test) to compare the learning outcomes of the two groups. The results of this study show that the application of the team quiz type cooperative learning model has an influence on the learning outcomes of grade XI students in Geography at SMAN 4 Palu. Based on results The research obtained the average score of student learning outcomes in the experimental class was 78.5 and the control class was 68.58. and data analysis that includes pretest and posttest tests using an inferential statistical formula at a significant level of 0.05. The calculated t-test is obtained t-count = 4.28 and the significant level a = 0.05 in t-table in 1.667 this means t-count > t-table. So that H0 is rejected and H1 is accepted. So it can be concluded that the team quiz type cooperative learning model has an effect on student learning outcomes. Therefore, it is recommended that teachers consider using this model in the learning process to improve student engagement and understanding.